1863. Treatment and Outcomes of Cefoxitin-Non-Susceptible Serratia marcescens, Klebsiella aerogenes, Citrobacter freundii, Enterobacter cloacae, and Morganella morganii Bacteremia with Piperacillin/Tazobactam Versus Cefepime or Carbapenem in Immunocompromised Patients. (15th December 2022) - Lu, Brian; Wong, Miranda; Diep, Calvin; Ha, David R; Bounthavong, Mark; Banaei, Niaz; Deresinski, Stan
Abstract: Background: A recent guidance suggested "caution if prescribing piperacillin-tazobactam for serious infections caused by organisms at high risk of significant AmpC production" and that the preferred antibiotic choice should be either cefepime or a carbapenem, despite an admitted lack of definitive evidence. Examination of this question in immunocompromised patients may provide such evidence. Methods: This was a retrospective, single-center study conducted from January 2016 to December 2021. We included immunocompromised patients aged 18 years or older who had a laboratory confirmed blood culture positive for Enterobacterales showing non-susceptibility to cefoxitin and were definitively treated with piperacillin-tazobactam, cefepime, or a carbapenem. The primary endpoint was a composite of clinical or microbiological failure, which was comprised of in-hospital 30-day mortality, white blood count >12 x 10 9 /L or temperature >38°C on days 5-7, microbiological failure on days 3-5, or microbiological recurrence/relapse on days 5-30. Results: We identified 81 patients who were included for analysis. Baseline characteristics between arms were similar between groups except for more frequent severe neutropenia (p=0.010) and higher Pitt bacteremia scores (p=0.042) in the cefepime/carbapenem group. Within the piperacillin/tazobactam arm, 17 of 35 (48.6%) had clinical or microbiological failure, compared to 17 of 46 (37.0%) patients in the carbapenem/cefepime arm (p=0.294). Microbiological failure occurred in 4 of 35 (11.4%) patients treated with piperacillin/tazobactam compared to 0 of 46 (0%) patients treated with a carbapenem/cefepime (p=0.019). In multivariate analysis, patients treated with a carbapenem/cefepime had a 69% lower odds of clinical or microbiological failure compared to those treated with piperacillin/tazobactam (OR = 0.31; 95% confidence interval, 0.10-0.98). Conclusion: In immunocompromised patients with bacteremia due to cefoxitin-non-susceptible Serratia marcescens, Klebsiella aerogenes, Citrobacter freundii, Enterobacter cloacae, or Morganella morganii, definitive treatment with piperacillin/tazobactam was associated with a higher likelihood of microbiological failure compared with treatment with a carbapenem or cefepime. Disclosures: All Authors : No reported disclosures.